Construction of Information Security System of Power Generation Enterprise - Ying Yu (Dianxin kexue)
In order to meet the current demands of building information security, while ensuring existing business systems available, based on information technology to achieve the goal of building security system, the existing network deployment structure system access mode, user habits of Guodian Chengdu Jintang Generation Co., Ltd., on behalf of units of power generation enterprises, were analyzed. Based on this analysis, a five-level business system, as the network management, border security protection, mobile access security, host security, application security, was designed for power generation enterprise security reinforcement. By introducing the construction process of advanced security system of Guodian Chengdu Jintang Generation Co., Ltd., the references were provided for other power generation enterprise information safety construction.